Education of Communities at The Earthquake And Tsunami Disaster in Kenagarian Pasar Baru Kecamatan Bayang Pesisir Selatan - Syafriani Syafriani (Fakultas MIPA Universitas Negeri Padang, 2019)
West Sumatra is an area with a high seismic level. Earthquakes can be sourced on land and sea. Earthquakes originating at sea can cause tsunamis. One area of ​​West Sumatra which is located near the coast is the Pasar Baru area, Bayang Pesisir Selatan District, where if an earthquake occurs in the sea it will have the potential for a tsunami to occur. Therefore, it is very important to provide knowledge to the people who live in areas prone to earthquakes and tsunamis, especially those close to the coast. The knowledge provided aims to help measure community preparedness in the event of a disaster. So that the community can be better prepared and alert in facing disasters and can minimize the impact of the disaster. With this preparedness evaluation, it is expected that the community will have knowledge about earthquake and tsunami disasters, the impacts of disasters and knowledge to be prepared for the disaster.